Exposure of Fat Mass Obesity Gene Polymorphism in Diabetes Mellitus Type-II Females of Hyderabad, Sindh - Shaikh, Farheen; Rafiq, Muhammad; Bhutto, Muhammad Aqeel; Naqvi, Syed Habib Ahmed (Journal of Liaquat University of Medical & Health Sciences, 2019)
OBJECTIVES: To analyse and compare fat mass obesity gene polymorphism from blood samples in females with T2DM and Non-diabetic healthy females in population of Hyderabad, Sindh. METHODOLOGY: A cross sectional comparative study was conducted at Institute of Biotechnology and Genetic Engineering University of Sindh, Jamshoro. The patients were recruited from Department of Medicine unit-II (LUH) Jamshoro/Hyderabad while non-Diabetic healthy females were recruited from society by filling Performa. The verbal and written consent was taken from all participants and explaining them about purpose of study. Finally blood sample for gene analysis and other biochemical tests were collected and stored in the laboratory at -20C. Total 100 females were included in this study out of which 50 were T2DM females and 50 were normal healthy females. RESULTS: FTO (fat mass obesity) gene has strong association with basal metabolic index (BMI), as BMI increases the risk of T2DM in females also increases. We observed minor allele A and T at rs9939609 in Type 2 diabetic females with significantly higher with difference of (p <0.05) as compared with control group. In the present study rs9939609 FTO variant is strongly associated with Type 2Diabeticfemales of Hyderabad, Sindh. CONCLUSION: In the present study rs9939609 FTO variant was strongly associated with Type 2 Diabetic females of Hyderabad, Sindh. The study was also aimed to aware the population about inherited FTO gene variant which might be possible to implement genetic screening of females with T2DM which will be help in prevention of T2DM in future.